PENGARUH JIGSAW DISERTAI POSITIVE REINFORCMENT TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA SMPN 8 PONTIANAK - Nurmala, Nurmala; Enawaty, Eny; Melati, Husna Amalya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine: 1) the difference of motivation and learning outcome students which were given learning withÂ cooperative learningjigsawtype with positive reinforcement to the students which given learning with conventional methods in environmental pollution material, 2) the magnitude of the influence of cooperative learningjigsaw type with positive reinforcement on learning outcomes students. The form of the research was quasy experimentÂ with nonequivalent control group design. Sample selection technique was cluster random sampling technique. Instrument of the research consisted of learning motivation questionnaire and learning outcome test. The results showed that there was a difference between learning motivation and students learning outcomes which were given learning with cooperative learningjigsaw type with positive reinforcement towards students which were given learning with conventional methods in environmental pollution material. Learning using cooperative learning jigsaw type with positive reinforcement on the material of environmental pollution in seventh grade of SMPN 8 Pontianak giving the influence student learning outcomes of 58.9% .Â Keyword:Jigsaw, Positive Reinforcement, Learning Motivation, Learning Outcome, Environmental Pollution.